Retrofit Of Miling Machine - Krejčí, Jan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
This thesis deals with rebuild of manual milling machine BF20L into CNC milling machine and control using PLC. All axes are powered by stepper motors and controled by Beckhoff equipment and industrial computer C6015-0010. For digital control is used TwinCAT3 software and structured text as a standart PLC language.
Keywords: milling machine; CNC; PLC; TwinCAT3